Independent and combined effects of airway remodelling and allergy on airway responsiveness - Wang, K.; Le Cras, T.; Larcombe, Alexander; Zosky, G.; Elliot, J.; James, A.; Noble, P. (Portland Press Ltd., 2018)
Airway remodelling and allergic inflammation are key features of airway hyperresponsiveness (AHR) in asthma; however, their interrelationships are unclear. The present study investigated the separate and combined effects of increased airway smooth muscle (ASM) layer thickness and allergy on AHR. We integrated a protocol of ovalbumin (OVA)-induced allergy into a non-inflammatory mouse model of ASM remodelling induced by conditional and airway-specific expression of transforming growth factor-a (TGF-a) in early growth response-1 (Egr-1)-deficient transgenic mice, which produced thickening of the ASM layer following ingestion of doxycycline. Mice were sensitised to OVA and assigned to one of four treatment groups: Allergy - normal chow diet and OVA challenge, Remodelling - doxycycline in chow and saline challenge, Allergy and Remodelling - doxycycline in chow and OVA challenge, and Control - normal chow diet and saline challenge. Airway responsiveness to methacholine (MCh) and histology were assessed. Compared with the Control group, airway responsiveness to MCh was increased in the Allergy group, independent of changes in wall structure, whereas airway responsiveness in the Remodelling group was increased independent of exposure to aeroallergen. The combined effects of allergy and remodelling on airway responsiveness were greater than either of them alone. There was a positive relationship between the thickness of the ASM layer with airway responsiveness, which was shifted upward in the presence of allergy. These findings support allergy and airway remodelling as independent causes of variable and excessive airway narrowing.